2015
DOI: 10.1016/j.immuni.2015.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17B Antagonizes Interleukin-25-Mediated Mucosal Inflammation

Abstract: SUMMARY The interleukin-17 (IL-17) family cytokines have emerged as critical players in inflammatory diseases. Among them, IL-25 has been shown to be important in allergic inflammation and protection against parasitic infection. Here we have demonstrated that IL-17B, a poorly understood cytokine, functions to inhibit IL-25-driven inflammation. IL-17B and IL-25, both binding to the interleukin-17 receptor B (IL-17RB), were upregulated in their expression following acute colonic inflammation. Individual inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
126
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(133 citation statements)
references
References 60 publications
3
126
4
Order By: Relevance
“…25 Recently, IL-17B was demonstrated to protect mice from infection, whereas IL-17E exacerbated infectious pathogenesis in mice. 65 IL-17E and IL-17B in colitis. Il-17E expression is downregulated in inflamed colons from IBD patients and DSS-treated mice.…”
Section: Il-17dmentioning
confidence: 99%
See 3 more Smart Citations
“…25 Recently, IL-17B was demonstrated to protect mice from infection, whereas IL-17E exacerbated infectious pathogenesis in mice. 65 IL-17E and IL-17B in colitis. Il-17E expression is downregulated in inflamed colons from IBD patients and DSS-treated mice.…”
Section: Il-17dmentioning
confidence: 99%
“…Recently, one study showed that IL-17B antagonized IL-17E-mediated inflammatory gene expression during colitis by inhibiting the binding of IL-17E to its receptor. 65 Although IL-17E and IL-17B bind to the same receptor, these two cytokines seem to antagonize one another through different mechanisms. The detailed signaling events mediated by these two cytokines (especially IL-17B) need to be addressed in future studies.…”
Section: Il-17 Family Cytokine-mediated Signaling Pathwaysmentioning
confidence: 99%
See 2 more Smart Citations
“…Although IL-17A can promote podocyte apoptosis and cytoskeletal disorganization [79,80] , IL-17A/F signalling can also promote protective immune responses against infection at epithelial surfaces [81,82] . Other IL-17 family cytokines, through engaging receptor complexes containing an IL-17RA subunit, also have protective functions at mucosal surfaces [83] . In murine diabetes, IL-17A and IL-17F protect against nephropathy and proteinuria by limiting podocyte injury through the phosphorylation of renal and hepatic AMP kinase, mediated by enhanced expression of activated microglia/macrophagerestricted whey protein domain protein in podocytes, macrophages and tubular epithelial cells, and by inducing podocyte IL-10 expression and an M2 phenotype in macrophages [84] .…”
Section: Discussionmentioning
confidence: 99%